2004
DOI: 10.1002/hipo.20020
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor NF‐κB activation after in vivo perforant path LTP in mouse hippocampus

Abstract: There is increasing evidence that transcription factors (TFs) play a critical role in maintaining later phases of hippocampal long-term potentiation (LTP). We have been led to study the role in synaptic plasticity of the powerful, yet generally unheralded, NF-kappaB TF because it may serve as both a signaling molecule after its activation at the synapse and then a transcription initiator upon reaching the nucleus. In the present study, we show that LTP activates NF-kappaB in the intact mouse hippocampus. Mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
57
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 34 publications
3
57
0
Order By: Relevance
“…Furthermore, recent studies have indicated the requirement of active NF-B for LTP, LTD, and spatial memory (Kaltschmidt et al 2006;Romano et al 2006). Moreover, employ-ing the same antibody approach as adapted in the present studies, Freudenthal et al (2004) demonstrated that NF-B is upregulated in the hippocampus following both high-frequency and low-frequency stimulation in vivo. Along with the recent identification of p65-containing protein complexes in synaptic terminals and their activity-mediated retrograde transport to the cell body, these properties of NF-B position this transcription factor ideally to translate synaptic activity into a transcriptional program driving subsequent plasticity (Kaltschmidt et al 1993;Meberg et al 1996;Mattson and Camandola 2001;Wellmann et al 2001;Meffert et al 2003).…”
supporting
confidence: 65%
See 3 more Smart Citations
“…Furthermore, recent studies have indicated the requirement of active NF-B for LTP, LTD, and spatial memory (Kaltschmidt et al 2006;Romano et al 2006). Moreover, employ-ing the same antibody approach as adapted in the present studies, Freudenthal et al (2004) demonstrated that NF-B is upregulated in the hippocampus following both high-frequency and low-frequency stimulation in vivo. Along with the recent identification of p65-containing protein complexes in synaptic terminals and their activity-mediated retrograde transport to the cell body, these properties of NF-B position this transcription factor ideally to translate synaptic activity into a transcriptional program driving subsequent plasticity (Kaltschmidt et al 1993;Meberg et al 1996;Mattson and Camandola 2001;Wellmann et al 2001;Meffert et al 2003).…”
supporting
confidence: 65%
“…Recent studies have implicated the transcription factor NF-B in hippocampal LTP, LTD, and spatial memory (Freudenthal et al 2004;Kaltschmidt et al 2006;O'Mahony et al 2006;Romano et al 2006;Vernon et al 2006). Thus, differential basal activities of this cardinal transcription factor in distinct neuronal subpopulations of the hippocampus have important implications for the nature of plasticity mobilized in each area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of NF-κB has been shown to be triggered by a wide variety of stimuli, such as glutamate depolarization, increase in intracellular Ca 2+ , neuropeptides, neural cell adhesion molecule, and cytokines (e.g., interleukin-1) (Freudenthal et al, 2004). NF-κB is activated in neurons and glial cells in a variety of acute and chronic neurodegenerative conditions (Epstein and Gelbard, 1999;Mattson, 2005).…”
Section: Discussionmentioning
confidence: 99%